Medical image computing and computer assisted intervention – MICCAI 2020 : 23rd International Conference, Lima, Peru, October 4-8, 2020, Proceedings.: 23rd International Conference, Lima, Peru, October 4-8, 2020, Proceedings. Part VI (2020) - Unknown
No abstract available